Calcium intake during pregnancy is associated with decreased risk of emotional and hyperactivity problems in five-year-old Japanese children. (3rd October 2021) - Takahashi, Keiji; Tanaka, Keiko; Nakamura, Yoshitaka; Okubo, Hitomi; Sasaki, Satoshi; Arakawa, Masashi; Miyake, Yoshihiro
ABSTRACT: Background: Recently, more attention has been paid to behavioral problems in children. However, for the most part, risk factors for these problems have yet to be determined. Objective: The current prebirth cohort study investigated the relationship between maternal calcium consumption during pregnancy and behavioral problems in five-year-old Japanese children. Methods: Subjects were 1199 mother-child pairs. Dietary intake during the preceding month was assessed using a self-administered diet history questionnaire. Emotional problems, conduct problems, hyperactivity problems, and peer problems were assessed using the Strengths and Difficulties Questionnaire. Logistic regression analysis was conducted to estimate odds ratios (ORs) and 95% confidence intervals (CIs). Results: Compared with the lowest quartile of maternal calcium intake, the highest was significantly associated with decreased risk of childhood emotional problems: the adjusted OR (95% CIs) was 0.46 (0.27–0.79, P for trend = 0.01). Higher maternal calcium intake during pregnancy was also independently associated with decreased risk of childhood hyperactivity problems; the adjusted ORs (95% CIs) in the first, second, third, and fourth quartiles of maternal calcium intake during pregnancy were 1 (reference), 0.52 (0.31–0.84), 0.58 (0.35–0.93), and 0.60 (0.37–0.97), respectively ( P for trend = 0.046). No such inverse associations were observed for childhood conduct problems or peer problems; the adjusted ORs (95% CIs) in the highest quartile of maternal calcium intake were 0.97 (0.64–1.47) for conduct problems and 1.11 (0.61–2.01) for peer problems. Conclusions: Maternal calcium intake during pregnancy may decrease the risk of childhood emotional and hyperactivity problems.